PATTERN OF LEUKAEMIA PATIENTS ADMITTED IN AYUB TEACHING HOSPITAL ABBOTTABAD - Khan, Tariq Mehmood (Journal of Ayub Medical College Abbottabad, 2016)
Background: Any tissue of the body can give rise to cancer. However, those tissues which multiply rapidly are at high risk of developing cancer and haematopoietic system is one of them. Neoplasms of this system are known as leukaemia and lymphoma, according to the types of white cells involved.Study of cancer patterns in different societies, however can contribute a substantial knowledge about the aetiology of cancer. The present Study was designed and aimed to estimate the frequency of different types of leukaemia in patients admitted in Ayub Teaching hospital Abbottabad. Methods: Data from the patients admitted at oncology Department of Ayub Teaching Hospital Abbottabad from 2010 to 2015 was collected and analysed to calculate cumulative and year-wise frequency of leukaemia and its major types. Frequency distribution with reference to gender and age was also calculated. Results: In our analysis about 16% patients had acute myelocytic leukaemia and 32% patients had acute lymphocytic leukaemia; while chronic myeloid leukaemia outnumbered chronic lymphocytic leukaemia (11% and 3%); Hodgkin lymphoma was seen in 18% cases while Non Hodgkin lymphoma (NHL) was present in 20% cases. Out of the total, 150 cases (75%) belonged to mountainous areas of Hazara, i.e., 40 cases belonged to Kohistan, another 40 cases were residents of Battagram, 45 cases belonged to hilly areas of Mansehra and 25 cases to Kaghan valley, while only 50 (25%) cases were from the plain areas of Abbottabad and Haripur districts, i.e., 20 and 30 cases respectively. Conclusion: Leukaemia is more common in hilly areas of Hazara, since majority of the cases belonged to well-known mountainous regions of Kohistan, Battagram, Kaghan or Mansehra and only few cases belonged to the plain areas of Abbottabad and Haripur districts. Keywords: leukaemia, lymphoma, myeloid leukaemia, lymphoid leukaemia